Treating relapsed or refractory Philadelphia chromosome-negative acute lymphoblastic leukemia: liposome-encapsulated vincristine - Davis T (Dove Medical Press, 2013)
Tyler Davis, Sherif S Farag Department of Internal Medicine, Division of Hematology and Oncology, Indiana University School of Medicine, Indianapolis, IN, USA Abstract: Acute lymphoblastic leukemia (ALL) remains a disease with poor outcomes in adults. While induction chemotherapy achieves a complete remission in almost 90% of patients, the majority will relapse and die of their disease. Relapsed ALL is associated with a high reinduction mortality and chemotherapy resistance, with allogeneic hematopoietic stem cell transplantation offering the only therapy with curative potential. However, there is no efficacious and well tolerated standard regimen accepted as a “bridge” to allogeneic stem cell transplantation or as definitive treatment for patients who are not transplant candidates. Vincristine is an active drug in patients with ALL, but its dose intensity is limited by neurotoxicity, and its full potential as an anticancer drug is thus not realized. Encapsulation of vincristine into sphingomyelin and cholesterol nanoparticle liposomes facilitates dose-intensification and densification to enhanced target tissues with reduced potential for toxicity. Vincristine sulfate liposome injection (VSLI) is associated with significant responses in clinically advanced ALL, and has recently been approved by the US Food and Drug Administration for treatment of relapsed and clinically advanced Philadelphia chromosome-negative ALL. This review provides an overview of the preclinical and clinical studies leading to the approval of VSLI for the treatment of relapsed and refractory ALL, and suggests potential areas of future clinical development. Keywords: vincristine, lymphoblastic leukemia, liposome